AIE-active non-conjugated poly(N-vinylcaprolactam) as a fluorescent thermometer for intracellular temperature imaging. Issue 1 (5th November 2019) - Saha, Biswajit; Ruidas, Bhuban; Mete, Sourav; Mukhopadhyay, Chitrangada Das; Bauri, Kamal; De, Priyadarsi
Abstract : Unprecedented photoluminescence, AIE and heat-induced emission characteristics of non-conjugated thermoresponsive PNVCL were unveiled for the very first time which eventually empowered PNVCL to act as an intracellular thermometer. Abstract : Since temperature is one of the most significant physiological parameters that dictate the cellular status of living organisms, accurate intracellular temperature measurement is crucial and a valuable biomarker for the diagnosis and treatment of diseases. Herein, we introduce the foremost example of a non-conjugated polymer as a next generation fluorescent thermometer which is capable of addressing the key shortcomings including toxicity and thermal-induced fluorescence quenching associated with π–π conjugated system-based thermometers developed so far. We revealed, for the first time, the unique photophysical and aggregation-induced emission (AIE) characteristics of well-known thermoresponsive poly( N -vinylcaprolactam) (PNVCL) devoid of any classical fluorophore entity. PNVCL underwent a coil to globular conformational transition in an aqueous medium and appeared to be fluorescent above its lower critical solution temperature (LCST) near body temperature (38 °C). Eventually, this intriguing aspect enabled higher cellular uptake of PNVCL at the LCST boundary. By virtue of the AIE effect, the thermo-induced aggregation phenomenon has been ingeniously utilized to apply PNVCL as a novel fluorescent thermometer for intracellular temperature determination.